The Pro-Competitive Consequences of Trade in Frictional Labor Markets - Hamid Firooz (Center for Economic Studies and ifo Institute (CESifo), 2023)
What are the pro-competitive consequences of trade in frictional labor markets? This paper develops and estimates a dynamic general equilibrium trade model to show that the interplay between endogenously variable markups in product markets and frictions in labor markets has important implications for aggregate as well as distributional consequences of trade. In particular, I show that once markups are allowed to respond to trade liberalization, unemployment and residual wage inequality rise almost three times more than in a model with constant markups (in the steady state). The presence of labor market frictions makes the pro-competitive gains from trade liberalization negative.
Keywords: F12; F16; E24; J64; L11; 330; international trade; variable markups; pro-competitive gains; labor elasticity of revenue; unemployment; residual wage inequality; firm size distribution